Hunted - Stiefvater, Maggie, 1981- (New York, NY : Scholastic Inc., 2014)
Four children have discovered that they have spirit animals, a rare bond between human and animal that has launched them on a quest to save their world. The team heads to the forests of Eura, where another Great Beast is hidden.
Keywords: Fantasy; Human-animal relationships -- Juvenile fiction; Metamorphosis -- Juvenile fiction; Paranormal fiction; Quests (Expeditions) -- Juvenile fiction; Wolves -- Juvenile fiction; Human-animal relationships; Metamorphosis; Paranormal fiction; Quests (Expeditions); Wolves; Fiction